Love's Cross - Faboya, Tinu (Evans Brothers (Nigeria Publishers) Ltd, 2010)
Love's Cross is a fiction written to portray that love at first sight could mean true love. Funmi who is naïve and quite new in the game of love is swept of her feet when Wole, a Lagos based business man makes to woo her
Keywords: Juvenile Fiction